INFLUENCE ENVIRONMENT WORK, TRAINING AND MOTIVATION ON EMPLOYEE PERFORMANCE OF PT. ERA MEDIKA ALKESINDO - Tedy Tandreas; Yenny Wijaya; Ellen Stone; Kristi Endah Ndilosa Ginting; Mella Yunita (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to test and analyze the Influence of Work Environment, Training, and Motivation on Employee Performance at PT. Era Medika Alkesindo. The research method used in this study uses a quantitative research method with a quantitative descriptive research type that is explanatory research . The population of this study were employees at PT. Era Medika Alkesindo totaling 62 people, the sample of this study was 62 respondents. The data analysis method used was regression linear multiple. Results study test f Where f count > f table with level significant < 0.05 shows that simultaneously the Work Environment, Training and Motivation simultaneously have a significant influence on the Employee Performance of PT. Era Medika Alkesindo. The results of the t-test study where the work environment that have influence positive and significant on Employee Performance at PT. Era Medika Alkesindo, Training that has a positive and significant influence on Employee Performance at PT. Era Medika Alkesindo and Motivation that has a positive and significant influence on Employee Performance at PT. Era Medika Alkesindo. The results of the determination coefficient analysis obtained an Adjusted R2 value of 0.508 , meaning that the variation of the Work Environment, Training, and Motivation variables is 50.8%, while the remaining 49.2% is explained by other variables.